Implementation and challenges of sustainable tourism programs in Bali - Januar, Rizky (Bali Tourism Journal, 2024)
The rapid growth of tourism in Bali has led to extensive development of accommodations, infrastructure, and facilities, positioning the island as a major tourist destination. However, this growth has brought significant challenges, including environmental degradation, cultural commodification, and social inequalities. The overexploitation of natural resources, unsustainable waste management, and deforestation have raised concerns about the island’s long-term ecological health. Additionally, the commercialization of cultural traditions and rising land prices have disrupted local communities and eroded the authenticity of Balinese heritage. In response, Indonesia has launched the "Decarbonization Roadmap for the Tourism Sector" to transition towards a more sustainable tourism model. This roadmap, supported by traditional values like Tri Hita Karana, emphasizes balancing economic growth with environmental preservation and cultural respect. Sustainable tourism practices such as community-based tourism and ecotourism are emerging as potential solutions, focusing on local participation and environmental conservation. Despite these efforts, significant challenges remain, including the uneven distribution of tourism benefits, income inequality, and the heavy reliance on tourism for Bali’s economy. Addressing these issues will require integrated and thoughtful approaches that prioritize sustainability and inclusive development.